Solar Hybrid Electric Vehicle - Muharram, Rami; Mujahid, Ashraf; Al-Baw, Mohammed (Palestine Polytechnic University - Department of Mechanical Engineering, 2017)
Abstract The development of vehicles with internal combustion engine, especially automobiles, is one of the greatest achievements of modern technology. Automobiles have made great contributions to the growth of modern society by satisfying many of its needs for mobility in everyday life. The rapid development of the automotive industry, unlike any other industry, has prompted the progress of human society from a primitive life to a highly developed industrial society. The automotive industry and the other industries are the backbone of the word’s economy as it employs the greatest share of the working population. However, the large number of automobiles in use around the world has caused and continues to cause serious problems for the environment and human life. Air pollution, global warming, and the rapid depletion of the Earth’s petroleum resources, these problems are now problems of paramount concern. In recent decades, most governorates are focusing on researches and developed activities related to transportation. The researches have emphasized on producing high efficiency, clean, and safe transportation, like the Electric vehicles . From here, we are discussing in this project the concept of a solar car that can accommodate a single passenger. This vehicle is equipped with solar panels on the top of it in order to let the energy from the sun enter and then transfer it to an electric energy that passes through energy control circuits, batteries to regulate the electric to suit the engine that manages the wheels of this vehicle. We believe in this design of this vehicle for several reasons, first light weight, durability and reliability in the selection of materials. الملخص إن تطور المركبات ذات محرك الاحتراق الداخلي وخاصة السيارات هي واحدة من أعظم إنجازات التكنولوجيا الحديثة حيث ساهمت السيارات في نمو المجتمع الحديث بشكل كبير من خلال تلبية العديد من احتياجاته من التنقل في الحياة اليومية. ساهم التطور السريع في صناعة السيارات وعلى عكس أي صناعة أخرى في دفع تقدم المجتمع البشري من حياة بدائية إلى مجتمع صناعي متطور للغاية ومن ناحية أخرى تُشكل صناعة السيارات وغيرها من الصناعات العمود الفقري للاقتصاد كما ويساعد على توظيف نسبة كبيرة من القوى العاملة ومع ذلك تسبب استخدام عدد كبير من السيارات في جميع أنحاء العالم في مشاكل خطيرة على البيئة وحياة الإنسان ومازالت هذه المشاكل تشكل الشغل الشاغل للعالم في العقود الأخيرة مثل تلوث الهواء والاحتباس الحراري والاستنزاف السريع لموارد البترول وفي الآونة الأخيرة , وبضغط من الحكومات تم التركيز في كافة البحوث وأنشطة التطوير المتعلقة في مجال النقل على تطوير وسيلة نقل ذات كفاءة عالية ونظيفة وآمنة وقد اقترحت السيارات الكهربائية. تم عرض السيارات الكهربائية الهجينة والسيارات التي تعمل بخلايا الوقود لتحل محل السيارات التقليدية في المستقبل القريب ونحن من خلال هذا البحث المنجز نعمل على وصف تصميم وتصنيع سيارة كهربائية أوتوماتيكية وتعمل على الطاقة الشمسية صُممت خصيصاً لذوي الاحتياجات الخاصة حيث لا تقتصر على هذه الميزة فقط، بل يمكن ان تستخدم لأغراض متعددة. من هنا فأننا في هذا المشروع اتجهنا الى فكرة مركبة تعمل على الطاقة الشمسية تتسع لراكب واحد وهي عبارة عن مركبة مزودة بالواح شمسيه على سطحها تقوم باستقبال اشعة الشمس وتحويلها الى طاقه كهربائية تمر هذه الطاقة خلال دوائر تحكم وبطاريات و تنظيم للتيار الكهربائي بما يناسب المحرك الذي يدير عجلات هذه المركبة , وراعينا في تصميم هذه المركبة عدة امور منها خفة الوزن و المتانة و الاعتمادية في اختيار المواد المكونة لمثل هذه العربة و هذا المشروع قابل للتطوير و التعديل .
CD 30174 , number of pages 85 ,ميكانيك 1/2017 , in the store
Keywords: Solar, hybrid, Electric, vehicle, Mechanical